Islamic religious education for children of Indonesian migrant workers: adaptive strategies at the Indonesian school guidance center in Kuala Lumpur, Malaysia - Robbani, Ikbar; Muliyah, Pipit (Jurnal Pendidikan Agama Islam Al-Thariqah, 2026)
This study aims to identify and analyze various adaptive strategies in teaching Islamic Religious Education (IRE) at Sanggar Bimbingan (SB) in the Kuala Lumpur area, Malaysia. Undocumented children of Indonesian Migrant Workers (PMI) face massive structural marginalization that closes their access to formal education. In these highly limited conditions, Sanggar Bimbingan serves as a crucial alternative educational space to prevent the "lost generation" phenomenon. This research employs a descriptive qualitative approach with data triangulation techniques involving a survey of eight International KKN practitioners across seven learning center locations, in-depth interviews with managers, and documentation studies of learning reports. The research results reveal that educators implement five main adaptive strategies as the pillars of learning: (1) curriculum transformation through functional material simplification focusing on daily worship practices; (2) the application of multigrade teaching to circumvent space limitations and teacher-to-student ratios; (3) differentiated instruction tailored to individual students' literacy levels and learning readiness; (4) a psychospiritual approach through emotional validation as an instrument for trauma healing due to psychosocial vulnerabilities; and (5) the integration of religious nationalism values to strengthen the Indonesian national identity in transnational areas. The study concludes that Adaptive Pedagogy which is flexible, crisis-responsive, and based on humanistic empathy is the key to educational resilience in marginal spaces. This strategy has proven effective not only in transferring religious knowledge but also in maintaining mental health and ensuring the continuity of students' academic rights through the legality of diploma documents. This research recommends the need to strengthen digital literacy and more adequate instructional facilities to optimize education for migrant children in the future.